An initial evaluation of the effectiveness of Intreo activation reforms - Elish Kelly; Séamus McGuinness; Paul Redmond; Michael Savage; John Walsh (The Economic and Social Research Institute (ESRI), 2019)
The research examines if reforms to Ireland's public employment services (Intreo) had an impact on exits from the Live Register.
Keywords: 330